Review of empirical studies on impact of religion, religiosity and spirituality as protective factors - Salgado, Ana C. (2014)
The purpose of this article is to review the empirical researches supporting the positive impact of religion, religiosity and spirituality as protective factors in various areas of human life. An analysis of each variable is performed individually and collectively. Among the conclusions of this work, researches show that they help people to have more self-esteem, are a source of strength and hope, are associated with greater satisfaction with life and spiritual well-being and increase the capacity for forgiveness. They provide emotional and social support, promote prosocial values, are associated with less use and abuse of drugs and less tendency to smoke. They help to have better physical and psychological health, contribute to prevention and help to speed recovery and promote tolerance to diseases. They help to decrease depression, anxiety, blood pressure and stress. They contribute to a better adaptation, help to cope with the disease and fear of death. Finally, they help to better deal with disability condition associated with chronic disease.